STRENGTHENING DIGITAL LITERACY FOR COMMUNITY-BASED MARINE TOURISM DEVELOPMENT ON UNTUNG JAVA ISLAND - Mudayat (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2026)
This Community Service activity aims to enhance the digital literacy capacity of tourism managers, fishermen, and local artisans through training on creating promotional content, utilizing social media, and managing sustainable family tourism packages. The implementation method uses a participatory approach, including coordination, training, mentoring, and evaluation stages. The activity intervention also includes the installation of eight fish aggregating devices (FADs) as family-friendly fishing spots and a means of restoring fish habitats degraded due to coral reef damage. The results of the activity show an improvement in participants' skills in creating digital content (photos, videos, and promotional narratives), the formation of a local creative group called Digital Ranger, and increased community involvement in online tourism promotion. In conclusion, the synergy between physical innovation through the development of marine tourism facilities and the strengthening of digital literacy can empower communities in managing tourism destinations. The novelty of this activity lies in the integration between the installation of artificial reefs as an ecotourism innovation and community-based digital literacy training, making Untung Jawa Island a model for developing competitive and sustainable coastal digital tourism villages.